'Don't call me an academic': Professional identity and struggles for legitimacy within the vocational field of events management higher education. (November 2019) - Dashper, Katherine; Fletcher, Thomas
Abstract: Events Management is a relatively new subject within universities, and is positioned as a vocational field with links to industry and practice. This paper considers the role of the academic within Events Management higher education, and how individuals within this field position themselves and make claims to legitimacy. Drawing on interviews with 16 Events Management academics in the UK, we identify three narrative strategies adopted by individuals in this field as they position themselves in relation to academic and professional identities. The three narrative strategies identified – the anti-academic, the traditional academic and the blended professional – illustrate the precarious and often unstable identities of those within vocational subjects. Individuals within Events Management experience difficulty in terms of both their professional and academic identities, and may rely on a mixture of both traditional (e.g. research and teaching) and industry metrics in their claims to status and legitimacy.